Implementasi Pemikiran Integrasi-Interkoneksi Keilmuan Ibnu Sina dalam Pendidikan Islam - Syihabuddin, Muhammad; Manggala, Kayan; Mahfudhoh, Roudhotul; Nurul Huda, Luthfi; Tara Nisawanda Duha Alfani, Adila (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
The presence of this article aims to review the concept of Islamic education thought initiated by the Islamic scholar Ibn Sina. Departing from modernization which brought the pace of Islamic education to progress and continue to develop, which is also inseparable from the ideas that support the course of the learning and teaching process, one of which is the concept of Ibn Sina's Islamic education methodology. This paper uses the literature study method, by examining the manuscript or text related to the title taken. The results of this study reveal that the Islamic education methodology described by Ibn Sina has an adequate level of relevance in the development of Islamic education starting from objectives, curriculum, learning methods, and the concept of the ideal teacher initiated by Ibn Sina. Apart from that, the most important part is integrating religious and general sciences so that there is no scientific dichotomy. The practice of studying religion and general sciences must be balanced to provide broad insights for students in developing their potential and leading to the attainment of worldly happiness and throws. So that the concept of a perfect human in Ibn Sina's view is realized.